Antifouling activity of peracetylated cholic acid, a natural bile acid derivative - Pérez, Miriam (2019)
The antifouling activity of peracetylated cholic acid (1), a bile acid derivative which was isolated in a previous work as a natural product from the Patagonian sponge Siphonochalina fortis, was evaluated in laboratory and field trials. Toxicity and settlement assays were performed with the mussel Mytilus edulis platensis, while the field trials were carried out by addition of the compound to experimental soluble-matrix paints, which were then tested in the sea. The results obtained in this work show that 1 has a good antifouling activity and low toxicity, and the paints aditivated with 0,6% Wt showed promissory performances in the field trials at the sea. These results confirm the previous hypothesis that the few acetylated and lipophilic bile acid derivatives isolated from marine invertebrates may act as natural antifoulants. Compound 1 is a natural, biodegradable product that can be easily prepared from cholic acid, which in turn can be isolated in industrial scale from cattle bile. All these facts make cholic acid a good scaffold for the preparation of derivatives, which can be natural product-like, effective and sustainable antifouling additives for marine paints and other applications.